2011
DOI: 10.2190/de.41.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Non-Medical Use of Prescription Drugs among Youth in an Appalachian Population: Prevalence, Predictors, and Implications for Prevention

Abstract: This article examines prevalence of non-medical use of prescription drugs (NMUPD) in a sample of elementary and high school students in an Appalachian Tennessee county. We found that lifetime prevalence of NMUPD (35%) was higher than prevalence of cigarette use (28%) and marijuana use (17%), but lower than lifetime prevalence of alcohol use (46%). We examined characteristics, as well as risk and protective factors in several domains, as predictors of NMUPD. For comparison, we also examined these characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…Consistent with prior research examining the effects of parental and school factors in adolescent prescription drug misuse (Ford, 2009;Ford & McCutcheon, 2012;Spoth et al, 2013), our analysis indicated that both high levels of parental and school attachment reduced the odds that youths had used prescription drugs. As with research indicating community ties can reduce prescription drug misuse (Cheng & Lo, 2012;Cranford et al, 2013;Collins et al, 2011) and the particular salience of community factors for rural youths (Clark et al, 2011), our analysis indicated several community-level factors reduced the likelihood of prescription drug use. At the bivariate level, having adult mentors in the community was associated with lower odds of using.…”
Section: Discussion/conclusionsupporting
confidence: 71%
See 2 more Smart Citations
“…Consistent with prior research examining the effects of parental and school factors in adolescent prescription drug misuse (Ford, 2009;Ford & McCutcheon, 2012;Spoth et al, 2013), our analysis indicated that both high levels of parental and school attachment reduced the odds that youths had used prescription drugs. As with research indicating community ties can reduce prescription drug misuse (Cheng & Lo, 2012;Cranford et al, 2013;Collins et al, 2011) and the particular salience of community factors for rural youths (Clark et al, 2011), our analysis indicated several community-level factors reduced the likelihood of prescription drug use. At the bivariate level, having adult mentors in the community was associated with lower odds of using.…”
Section: Discussion/conclusionsupporting
confidence: 71%
“…Adolescents with strong bonds to their parents have also been found to be at decreased risk for misusing certain prescription drugs such as Ambien, one of the most commonly prescribed sedatives (Ford & McCutcheon, 2012). Other studies have documented an association between parental monitoring, closeness, and/or disapproval of substance use and reduced nonmedical prescription drug use (Barnes, Hoffman, & Welte, 2006;Cheng & Lo, 2012;Collins et al, 2011;Ford, 2009;King et al, 2013). Furthermore, there have been prevention programs, such as the one initiated by Fang and Schinke (2013), that have specifically focused on the protective mechanisms surrounding healthy parent-child relationships and have been associated with decreased use of illicit prescription drugs.…”
Section: Correlates Of Nonmedical Prescription Drug Usementioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to expectations, maternal warmth was associated with higher risk of nonmedical prescription drug use among Hispanic respondents, specifically (Harrell and Broman, 2009). Collins and colleagues did not detect an association between offspring reports of parental monitoring and any nonmedical prescription drug use in a sample of Appalachian children and adolescents (Collins et al, 2011). To our knowledge, no prior national study has examined the association between the quality of reciprocal maternal-offspring attachment, measured from the perspectives of both the mother and the offspring, and nonmedical prescription opioid use.…”
Section: Introductionmentioning
confidence: 97%
“…Rural communities may be particularly at risk with studies finding time spent with peers outside of the school day and lack of participation in extracurricular activities to be associated with the recreational use of prescription drugs among youth [27]. Finally, many individuals may not recognize the dangers of prescription or OTC drug abuse [7,28]. Data from the National Institute of Drug Abuse (NIDA)'s 2014 Monitoring the Future survey demonstrated that, though teens did not misuse or abuse prescription stimulants at higher rates than in the past, there was an overall decline in perceived risk of doing so.…”
Section: Prescription and Over-the Counter Drug Use In The United Stamentioning
confidence: 99%